Understanding selenium metabolism in plants and its role as a beneficial element. Issue 21 (2nd November 2019) - Chauhan, Reshu; Awasthi, Surabhi; Srivastava, Sudhakar; Dwivedi, Sanjay; Pilon-Smits, Elizabeth A. H.; Dhankher, Om P.; Tripathi, Rudra D.
Abstract: Selenium (Se) is an essential element for many animals including humans, prokaryotes and a few green algae. For plants, Se essentiality is yet to be demonstrated. Nevertheless, it is well recognized that Se is a beneficial element for plants. For all organisms, while, a narrow range of Se is beneficial, at elevated levels it becomes toxic. This is due to accumulation of various toxic inorganic and organic Se forms during Se metabolism as well as nonspecific replacement by Se of chemically similar sulfur (S) analogs. Interestingly, Se can act both as an antioxidant and a pro-oxidant. Hence, Se chemistry and metabolism play crucial roles in determining its effects at specific concentration in an organism. A lot of knowledge has been gained regarding Se metabolites, however, the functions of many of these metabolites are yet to be resolved. Other Se containing metabolites and proteins might yet be awaiting their identification. Future research in this direction would pave the way towards identification of Se as an essential element for plants too. This review discusses the various aspects of Se uptake and metabolism with a major focus on functions of Se-containing metabolites in plants.